2021
DOI: 10.3346/jkms.2021.36.e112
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Diabetes and Prediabetes Prevalence among Korean Adolescents From 2007 to 2018

Abstract: Background To provide updated prevalence data and to estimate changes in the prevalence of diabetes among Korean adolescents by sex and age between 2007 and 2018. Methods We used the data of children and adolescents (8,718 subjects aged 10 to 18 years) from the Korea National Health and Nutrition Examination Survey IV–VII (KNHANES 2007–2018). The recent prevalence of diabetes and pre-diabetes was estimated by using the latest KNHANES VII. The linear trends were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…YOD shares common risk factors for late-onset T2DM. In this respect, it is evident that the increasing prevalence of YOD is associated with an increase in people who are overweight or obese worldwide [ 11 , 12 ]. According to the KNHANES study of 2005 to 2014, obese individuals aged 10 to 29 years showed a seven-fold higher prevalence of diabetes than non-obese individuals at the same age [ 7 ].…”
Section: Risk Factors and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…YOD shares common risk factors for late-onset T2DM. In this respect, it is evident that the increasing prevalence of YOD is associated with an increase in people who are overweight or obese worldwide [ 11 , 12 ]. According to the KNHANES study of 2005 to 2014, obese individuals aged 10 to 29 years showed a seven-fold higher prevalence of diabetes than non-obese individuals at the same age [ 7 ].…”
Section: Risk Factors and Clinical Characteristicsmentioning
confidence: 99%
“…According to the KNHANES study of 2005 to 2014, obese individuals aged 10 to 29 years showed a seven-fold higher prevalence of diabetes than non-obese individuals at the same age [ 7 ]. The prevalence of diabetes was 0.19%, 0.34%, and 1.06% among normal-weight, overweight, and obese South Korean adolescents aged 10 to 18 years, respectively [ 12 ].…”
Section: Risk Factors and Clinical Characteristicsmentioning
confidence: 99%
“…From 2016 to 2018, in South Koreans aged 10 to 18 years, the prevalence of diabetes was 0.43% [ 48 ], and ours is one of the countries with the lowest incidence of diabetes. However, the prevalence of diabetes in our study population is high, and similar finding has already been reported by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia and insulin deficiency can affect bone cell functions, as well as the bone marrow fat, thus impairing the bone strength, geometry, and microarchitecture (9). With the epidemic of childhood obesity, the prevalence of prediabetes among children and adolescents has increased over the past decade (10). Unlike adults, Pollock et al found that total body bone mineral content (BMC) was 4% lower in overweight children with prediabetes than in those without prediabetes (11).…”
Section: Introductionmentioning
confidence: 99%